How to save Bergen from the sea? Decisions under uncertainty. Issue 2 (16th April 2018) - Guttorp, Peter; Thorarinsdottir, Thordis L.
Abstract : Sea level rise poses a threat to the Norwegian coastal city of Bergen and its historic harbour. The threat could be reduced, but greater flood protection comes at greater cost. And, of course, no one knows for certain how far sea level will rise in future. Decision‐makers must therefore decide what to do, and how much to spend, without knowing exactly how bad things could get. Peter Guttorp and Thordis L. Thorarinsdottir explain the problem, and how to deal with the uncertainty Abstract : Sea level rise poses a threat to the Norwegian coastal city of Bergen and its historic harbour. The threat could be reduced, but greater flood protection comes at greater cost. And, of course, no one knows for certain how far sea level will rise in future. Decision‐makers must therefore decide what to do, and how much to spend, without knowing exactly how bad things could get. Peter Guttorp and Thordis L. Thorarinsdottir explain the problem, and how to deal with the uncertainty.